The trader's guide to key economic indicators - Yamarone, Richard (Hoboken, N.J. : Bloomberg Press, 2012)
A handy reference to understanding key economic indicators and acting on themNew economic data are reported virtually every trading day. Investors, big and small, have to understand how these reports influence their investments, portfolios, and future sources of income. The third edition of The Trader's Guide to Key Economic Indicators examines the most important economic statistics currently used on Wall Street. In a straightforward and accessible style, it tells you exactly what these reports measure and what they really mean. Filled with in-depth insights and practical advice, this reliable.
Acknowledgments -- Introduction -- Chapter 1. Gross domestic product -- Chapter 2. Indexes of leading, lagging, and coincident indicators -- Chapter 3. The employment situation -- Chapter 4. Industrial production and capacity utilization -- Chapter 5. Institute for Supply Management indexes -- Chapter 6. Manufacturers' shipments, inventories, and orders -- Chapter 7. Manufacturing and trade inventories and sales -- Chapter 8. New residential construction -- Chapter 9. Conference Board Consumer Confidence and University of Michigan Consumer Sentiment indexes -- Chapter 10. Advance monthly sales for retail and food services -- Chapter 11. Personal income and outlays -- Chapter 12. Consumer and producer price indexes -- Chapter 13. The fixed-income market -- Chapter 14. Commodities -- About the author -- Index.
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher.
Keywords: Economic indicators -- United States; Investments -- United States; BUSINESS & ECONOMICS / Finance; Economic indicators -- United States; Investments -- United States; Business; Economic indicators -- United States; Investments -- United States; Economic indicators; Investments; Economic indicators / United States; Investments / United States; United States; Electronic books; Electronic books